MATURE SETARIA LABIATO-PAPILLOSA IN CATTLE – A SOURCE FOR RECEIVING ANTIGENS FOR DIAGNOSIS OF DIROFILARIASIS (DIROFILARIA IMMITIS) - V. K. Berezhko; V. K. Khaydarov; L. A. Napisanova; A. A. Thakahova (Российский паразитологический журнал)
Objective of research:   to estimate the efficacy of fractionated antigen of mature cattle parasites Setaria labiato-papillosa in diagnosis of dirofilariasis (Dirofilaria immitis).Materials and methods:  Antigens of mature Setaria labiato-papillosa, reference sera from infected and not infected dogs. Reaction of immunodiffusion (RID) in agar gel using reference sera from dogs infected with D. immitis, and extracts from S. labiato-papillosa and D. immitis. Gel-chromatographic method on Pharmacia columns of Superose 12 Prep Grade and immunoenzymatic reaction (IER).Results and discussion: The reaction of immunodiffusion (RID) was used to detect cross-reacting antigens of D. immitis and  S. labiato-papillosa.  The fractionation of antigen-extract from S. labiato-papillosa allows to get 40 protein fractions, 7 (17,5%) of which were of interest for diagnosis of dirofilariasis. The evaluation of these fractions with respect to diagnosis of dirofilariasis was performed  by immunoenzymatic reaction with 47 serum samples from dogs including 11 serum samples from D. immitis infected dogs; 6  D. repens; 3 – Babesia canis; 3 – Toxocara canis; 9samples from dogs with non-parasitic pathology and 15 – from clinically healthy dogs. These results revealed that in one of 11 serum samples infected by D. immitis, and in two of 6 serum samples infected by D. repens a false-negative response has been registered.The test sensitivity was 82,4%, the specificity – 83,3%. The sensitivity of the similar test with these sera using the purified antigen extract from mature D. immitis, was also 82,4%, and the specificity – 86,7%.The comparability of diagnostic test results for dirofilariasis by IER using antigenic preparations from Setaria and Dirofilaria allows to come to a conclusion that it is possible to use S. labiato-papillosa as a source of antigen for diagnosis of dirofilariasis (D. immitis).